SISTEM PENUNJANG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK PT. MITRA INFOSARANA - Joycelin Joycelin; Dali Santun Naga; Dedi Trisnawarman (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
The selection of the best employees in the company aims to provide rewards in the form of bonuses or salary increases and even promotions. This is intended to encourage each employee to always provide the best performance for the company in carrying out their duties and obligations. The application of the best employee decision support system is made with a Weighted Product method that aims to facilitate company leaders in determining the best employees to be rewarded. Based on the results of the tests conducted, 90% of the testers said that the application of the best employee decision support system has complete and good features in using this application. The conclusion is that the best employee decision support system application program PT. This Infosarana Partner can facilitate PT. Infosarana partners in determining the best employees who will be given rewards from each division